Exploring Nursing Students’ Perception on Online Class with the Implementation of TPACK Framework within Task-based Language Teaching - Fitri Handayani; M. Zaim; Hermawati Syarif; Yetty Zainil (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
The purpose of this study is to explore nursing students' perceptions of the use of the TPACK Framework within Task-based Language Teaching in an online class. The study employed a one-shot survey design. The participants of this study were 40 undergraduate nursing students at the nursing study program Poltekes Solok, West Sumatera. To avoid teacher-centered learning, this study implemented the TPACK Framework within Task-based Language Teaching, which has the potential to modify the way students learn. The questionnaire was delivered to the students using Google forms after the online learning activities were completed. The questionnaire was statistically analyzed using descriptive statistics such as frequency and percentage. The findings showed that most nursing students had positive perceptions of the use of the TPACK Framework within Task-based Language Teaching in online classes. Thus, incorporating the TPACK Framework into Task-based Language Teaching may become one of the potential methods of teaching English for nursing in an online class.